2013
DOI: 10.1038/ijos.2013.46
|View full text |Cite
|
Sign up to set email alerts
|

Oral epithelial stem cells in tissue maintenance and disease: the first steps in a long journey

Abstract: The identification and characterization of stem cells is a major focus of developmental biology and regenerative medicine. The advent of genetic inducible fate mapping techniques has made it possible to precisely label specific cell populations and to follow their progeny over time. When combined with advanced mathematical and statistical methods, stem cell division dynamics can be studied in new and exciting ways. Despite advances in a number of tissues, relatively little attention has been paid to stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 92 publications
0
82
1
3
Order By: Relevance
“…Rola nowotworowych komórek macierzystych w indukcji i progresji nowotworów Nowotworowe komórki macierzyste (CSCs -cancer steam cells) definiuje się na podstawie ich zdolności do formowania drugorzędowych guzów, po ich wyizolowaniu z guza pierwszorzędowego i przeszczepieniu do myszy z obniżoną odpornością (16).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…Rola nowotworowych komórek macierzystych w indukcji i progresji nowotworów Nowotworowe komórki macierzyste (CSCs -cancer steam cells) definiuje się na podstawie ich zdolności do formowania drugorzędowych guzów, po ich wyizolowaniu z guza pierwszorzędowego i przeszczepieniu do myszy z obniżoną odpornością (16).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…Many studies widely demonstrated the promising in vitro and in vivo TR potential of the oral MSCs. Noteworthy, the oral cavity contains different "niches" of stem cells: dental pulp from permanent and deciduous teeth, periodontal ligament, dental follicle, apical papilla and the three subtypes of mucosa: the masticatory mucosa, namely hard palate and gingiva; the specialized mucosa, represented by the dorsal surface of the tongue, and the lining mucosa, which includes buccal mucosa, the internal surface of the lips, the ventral surface of the tongue, the soft palate, and the alveolar mucosa [9][10][11][12][13][14][15][16] .…”
Section: Oro-facial Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The demonstrated great potential of SHEDs and OMSCs 16,17,[24][25][26] and the relatively easy collecting and harvesting method, led us to suggest the opportunity to use the deciduous teeth, naturally lost in pediatric age, and/or the oral mucosa, for TR purposes of patients.…”
Section: Oro-facial Mesenchymal Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations